2011
DOI: 10.1093/infdis/jir307
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Preterm Delivery Among HIV-Infected Women Randomized to Protease Versus Nucleoside Reverse Transcriptase Inhibitor-Based HAART During Pregnancy

Abstract: PI-based HAART was associated with increased preterm delivery but not increased infant hospitalizations or mortality in a clinical trial setting. The association between PI use and lower increase in BMI in late pregnancy warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(113 citation statements)
references
References 22 publications
(30 reference statements)
8
102
3
Order By: Relevance
“…A study by the Agence Nationale de Recherche sur le Sida (ANRS) of France showed an increased rate of PTB among women treated with boosted versus unboosted PI (aHR 2.03, 95% CI 1.06–3.89), more specifically with respect to spontaneous delivery [25]. Our PTB rate of 19.3% among women treated with boosted PIs is also similar to that found in the Mma Bana study (21.4%) from Botswana, where all women in the PI treated arm received LPV-r during pregnancy [26]. In light of previous conflicting reports between North American and European cohorts, the concordance of our findings to the French perinatal cohort is reassuring.…”
Section: Discussionsupporting
confidence: 64%
“…A study by the Agence Nationale de Recherche sur le Sida (ANRS) of France showed an increased rate of PTB among women treated with boosted versus unboosted PI (aHR 2.03, 95% CI 1.06–3.89), more specifically with respect to spontaneous delivery [25]. Our PTB rate of 19.3% among women treated with boosted PIs is also similar to that found in the Mma Bana study (21.4%) from Botswana, where all women in the PI treated arm received LPV-r during pregnancy [26]. In light of previous conflicting reports between North American and European cohorts, the concordance of our findings to the French perinatal cohort is reassuring.…”
Section: Discussionsupporting
confidence: 64%
“…Advanced maternal HIV disease is recognized as risk factor for LBW and PD according to the report of many studies [15,31,32]. Studies from Kenya also showed that HIV-infected women were 3 times more likely to deliver a LBW baby in the presence of HIV-related symptoms and lower CD4 level [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analyses were conducted to adjust for prematurity 35 and low birth weight. Since these birth characteristics could be on the causal pathway between in utero ARV exposure and later cognitive or academic functioning, they were not considered in the primary analyses.…”
Section: Methodsmentioning
confidence: 99%